Old Practice, but Young Research Field: A Systematic Bibliographic Review of Personal Branding - Scheidt, Stefan; Gelhard, Carsten; Henseler, Jörg (Frontiers in Psychology, 2020)
Before engaging with the already intensive and still increasing personal branding activities in many fields of practice, a scholarly approach would call for a more specific definition of the concept of personal branding processes and the resulting human brands. A multi-step analysis of the growing body of literature on personal branding is employed, integrating a framework that covers six key research streams of personal branding, (1) terminology and definition, (2) underlying theories, (3) classes and categories, (4) benefits, (5) antecedents, and (6) key ingredients and applications, complemented by challenges the domain of personal branding has to cope with. The analysis shows that personal branding is an interdisciplinary concern, which is still in its infancy and in which universally valid personal branding frameworks or even theories cannot be identified yet. Personal branding appears as a source for new academic impulses, as it may sensitize scholars to opportunities for intensifying collaboration with practitioners and with other academic domains to enrich and disseminate knowledge in their fields.